2017
DOI: 10.5352/jls.2017.27.5.567
|View full text |Cite
|
Sign up to set email alerts
|

Production of gamma-Aminobutyric Acid (GABA) by Lactobacillus plantarum subsp. plantarum B-134 Isolated from Makgeolli, Traditional Korean Rice Wine

Abstract: This study is to isolate and identify γ-amino butyric acid (GABA) producing lactic acid bacteria (LAB) from Makgeolii, traditional Korean rice wine and then establish the optimal culture conditions for GABA production. Sixty four LAB from Makgeolli were isolated according to the characteristics of the shape and color of the colony grown on MRS agar plate. The GABA production of the isolated strain cultured in MRS broth contained 1% MSG (mono-sodium glutamate) were determined and evaluated by TLC and HPLC analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…In a study by Lee et al (2017), an incubation temperature of 30°C during the lactic fermentation was shown to induce a sharp decrease in pH over 24 h. However, the decrease in pH observed in this study was minimal after 1 day of lactic fermentation. Generally, lactic fermentation leads to a lower pH and increased acidity since fermentable sugars are used to produce lactic acid.…”
Section: Resultscontrasting
confidence: 52%
“…In a study by Lee et al (2017), an incubation temperature of 30°C during the lactic fermentation was shown to induce a sharp decrease in pH over 24 h. However, the decrease in pH observed in this study was minimal after 1 day of lactic fermentation. Generally, lactic fermentation leads to a lower pH and increased acidity since fermentable sugars are used to produce lactic acid.…”
Section: Resultscontrasting
confidence: 52%
“…L-G7, while the strains isolated from T. molitor larvae, P. brevitarsis larvae, and A. dichotoma larvae were identified and designated as E. avium No-22-1, Enterococcus avium HJ-N6, and Enterococcus avium JS-N6B4, respectively. Most GABA-producing microbes have been isolated from traditional fermented foods such as kimchi [11,12], makgeolli [13], fish products [14], cheese [15][16][17], sourdough [18], and paocai [19]. These sources generally provide an acidic environment and contain high levels of glutamate, a GABA precursor.…”
Section: Phylogenetic Identification Of Gaba-producing Strains From Ementioning
confidence: 99%
“…Several studies have evaluated microorganisms that produce GABA, particularly Korean fermented foods such as kimchi [11,12], makgeolli [13], fish products [14], cheese [15][16][17], and sourdough [18] as well as Chinese fermented foods such as paocai [19]. Studies have also been conducted to maximize GABA production from isolated strains, and using recombinant enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to improve fermenting microorganism strains and develop novel fermentation processes are actively underway to increase the value of using GABA in functional foods and medicines. In addition, efforts are being made to strengthen functionality and increase the product value of fermented foods, such as soybean products, shrimp, cheese, makgeolli (Korean rice wine), and kimchi, by using microorganisms that produce GABA in the starter cultures for these products [ 18 - 22 ].…”
Section: Introductionmentioning
confidence: 99%